Hubungan Masyarakat dengan Administrasi Pendidikan - Firmansyah, Alief; Prayuda, Denny; Setyadi, Breadley (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The relationship between public relations and educational administration as two key elements in improving the quality of education and relations between schools and society. The research method used is library research which involves topic identification, literature search, literature selection, and in-depth analysis of the selected literature. The research results show that public relations has an important role in mediating communication between schools and the community, ensuring good understanding of school goals and programs, and winning community support and involvement in improving educational standards.